Investigating the effect of the equivalent conicity function's nonlinearity on the dynamic behaviour of a rail vehicle under typical service conditions. Issue 10 (3rd October 2022) - Kulkarni, Rohan; Qazizadeh, Alireza; Berg, Mats; Dirks, Babette; Persson, Ingemar
Abstract : Generally, the equivalent conicity function (ECF) is denoted by equivalent conicity at 3mm (λ3mm ) and a Nonlinearity Parameter (NP). NP describes the nonlinearity of the ECF and its influence on a vehicle design is explored thoroughly, however, NP's role in vehicle and track maintenance is not researched yet. This paper investigates the influence of track maintenance actions on vehicle dynamics with help of NP vs λ3mm scatter plots of ECF database. The ECF database is constructed by combining measured worn wheel and rail profile pairs of the Swedish high-speed vehicle and rail network, respectively. The ECF database revealed an inverse relationship between λ3mm and NP, i.e., NP is negative for larger λ3mm values. The combination of negative NP and high λ3mm causes reduction in the vehicle's nonlinear critical speed and vehicle often exhibit the unstable running on the Swedish rail network. Thus, the occurrence of ECF with negative NP and high λ3mm  is undersirable and the undesirable ECF can be converted into desirable ECF by grinding the rail, which converts ECF's into positive NP and low λ3mm combinations. Thus, the NP parameter along with the λ3mm must be considered in track maintenance decisions.